A PRISMA systematic review and meta-analysis on Chlamydia trachomatis infections in Iranian women (1986–2015). Issue 16 (April 2018) - Roshani, Daem; Ramazanzadeh, Rashid; Farhadifar, Fariba; Ahmadi, Amjad; Derakhshan, Safoura; Rouhi, Samaneh; Zarea, Shamsi; Zandvakili, Farnaz
Abstract: Background: Chlamydia trachomatis (CT) is the cause of genital tract infections in women. Some evidence has shown the role of this infection with CT in spontaneous abortions. The purpose of this study is to study the frequency of CT infection in Iranian women. Methods: This study was performed based on PRISMA guidelines. A total of 75 articles published in Google Scholar, PubMed, ISI Web of Science, Biological abs, Iranmedex, SID, and Scopus databases were found (1986–2015) using the following keywords: CT in women, CT and Iranian women, CT and infection in Iran, CT and pregnancy in Iran, CT and preterm delivery in Iran, CT and preterm labor in Iran, CT and fertility in Iran, CT and infertility in Iran, and CT and abortion in Iran. Finally, 40 studies from different regions of Iran were included. Statistical analyses were performed using R3 and STATA 12. Results: From 1986 to 2015, the lowest rate of prevalence was from 2010 to 2011 (3.9%) and the highest prevalence rate was in 2009 (69.39%) in northern Iran. Fixed effects for different parts of Iran (North, South, East, and West) were Pooled proportion: 0.13 (95% confidence interval [CI] = 0.12–0.14) and for samples (cervical, vaginal, urine, and blood) the pooled proportion was = 0.14 (95% CI = 0.12–0.14). Conclusion: CT infection in this study was prevalent in urine samples and the rate of CT was observed from culture methods in comparison to other methods. Because women with CT play an important role because of sexual activity for transmission and untreated women are at risk of developing sequels. Also, most studies in Iran use sensitive polymerase chain reaction tests for the detection of genital CT infections.